Efeito da combinação do treinamento físico aeróbio e carvacrol sobre modulação do sistema renina-angiotensina-aldosterona na hipertensão arterial sistêmica - SILVA, Daiane Pereira da (2022)
Objective: To evaluate the effect of the combination of aerobic physical training and carvacrol on modulation of the renin-angiotensin-aldosterone system in systemic arterial hypertension. Method: 6 groups were used, each with 6 animals: G1- Wistar-normotensive control treaded with sorbitol; G2- SHR hypertensive control treated with sorbitol; G3- SHR- treated with losartan (50mg); G4- SHR- treated with carvacrol (20mg); G5-SHR- trained with 60 minutes aerobic exercise; G6-SHR- treated with carvacrol (20mg) + 60 minutes of aerobic exercise. The animals received treatment with administration by gavage for 4 weeks and a protocol of aerobic exercise being the intensity adjusted each week and with weekly recording of weight, feed consumption, heart rate, systolic, diastolic and mean blood pressure. At the end of treatment, biochemical measurements were performed for renal, hepatic, lipid parameters and serum levels of angiotensin 1-7 and ACE I. Results: of the hypertensive animals, and the hypertension was controlled after 4 weeks of intervention. The Exercarv group presented greater magnitudes of BP reduction, when compared to the other groups, presenting pressure values of SBP 122.0 ± 3.8 mmHg, DBP 97 ± 3.0 mmHg, MAP 105.5 ± 2.3 mmHg. Furthermore, the ExerCarv group caused reductions in TG, CT, VLDL, TG/HDL and CT/HDL levels, as well as urea and AST levels. The treatment with carvacrol alone, as well as its combination with aerobic physical training, were able to reduce ACE I activity compared to the SHR group with p<0.001. Ang 1-7 showed no increase, but did not differ statistically from normotensive animals. Discussion: Our findings show that four weeks of aerobic physical training combined with oral administration of carvacrol 20mg/kg/day shows antihypertensive action. With improvements in lipid levels and markers of liver and kidney function. Furthermore, it is suggested that carvacrol combined with aerobic training exerts antihypertensive action by inhibiting ACE I, thus modulating the RAAS, without the influence of the counter-regulatory arm of Ang 1-7. Conclusion: Four treatments of carvacro of intensive aerobic exercise training with anti-hyper effect combined with combined weeks of ACE. In addition, the treatment improved liver and lipid parameters.